Factors influencing desired family size among women of childbearing age in eastern Indonesia: Evidence from the Indonesian Demographic Health Survey - Cindy Ade Aulia; Siti Nurrochmah; Lucky Radita Alma; Supriyadi Supriyadi (Public Health and Occupational Safety Journal, 2025)
Background: Globally, Indonesia is the fourth most populous country. Based on the results of the Indonesian Central Bureau of Statistics census, it is known that the population of Indonesia in 2017 was around 261 million people, with an average number of children desired by women of childbearing age in East Nusa Tenggara Province of 2.9 or around three children per woman of childbearing age. Objectives: This study aimed to determine the relationship between marital status, age at first marriage, employment status, and the number of children desired. Methods: This quantitative study uses a cross-sectional design and an observational analytic survey method. This study took survey data from the 2017 Indonesian Demographic and Health Survey. The study sample was women aged 15-49 years who were recorded as a selected sample in East Nusa Tenggara Province, totaling 1,929 women. Data analysis used the Chi-square test. Results: The analysis showed that the p-value of marital status was 0.000, the p-value of age at first marriage was 0.000, and the p-value of employment status was 0.000, which means that there is a significant relationship between marital status, age at first marriage, and employment status with the number of children desired by women of childbearing age. Conclusions: This study found that marital status, age at first marriage, and employment status were significantly associated with the number of children desired by women of childbearing age. The findings suggest the need for employment-based interventions and marriage education to reduce fertility preferences in areas with high TFR.